CD44 gene rs9666607 polymorphism is associated with papillary thyroid carcinoma and interacts with CREB3L1 - Lili Ma; Xia Qu; Xinxi Li; Ye Tian; Bowei Wang; Borong Qiang; Sheng Jiang; Jianling Bao; Guoli Du (Tissue and Cell, 2026)

Inverse design of multi-frequency bandgaps for multi-modal vibration control in long-span bridge cables - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Copper and zinc isotopes reveal redox-driven nutrient cycles in the Mesoproterozoic ocean - Kexin Song; Dandan Li; Chengshuai Yuan; Yang Liu; Yuan-Ru Qu; Sheng-Ao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Electric-field-assisted minute-scale deep phosphate removal in a flow-by capacitive deionization system - Yue Jiang; Wentao Xiao; Lihan Sheng; Chenyiyi Qian; Yunfei He; Xuetong Qu; Jiafeng Ding; Hangjun Zhang (Journal of Environmental Chemical Engineering, 2026)

Dynamic changes in suitable production areas of Angelica sinensis (Oliv.) Diels under environment and land use policies - Liu Jia; Qu Cheng; Pu Chunjuan; Liu Pei; Guo Sheng; Zhou Guisheng; Duan Jin-ao; Zhao Siyi; Feng Yanzhe; Yan Hui (Journal for Nature Conservation, 2026)

Association between mixed metal exposure and depressive symptoms in the elderly: The moderating role of magnesium and mediating role of amino acids - Qianru Xie; Miaomiao Wei; Weixuan Yang; Mingzhi Liu; Kaiyong Liu; Qu-nan Wang; Sufang Wang; Fangbiao Tao; Jie Sheng (Environmental Pollution, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Decision-making for UAV–USV cooperative collision avoidance based on an improved PPO algorithm - Sheng Qu; Wei Guan; Tongbo Hu; Shuhui Hao; Xianku Zhang (Ocean Engineering, 2026)

Tuned pile vibration isolation method for near-field rail transit based on the negative effective mass density model for a dual-resonator system - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

USV autonomous collision avoidance strategy via GMM-distributional soft actor-critic in complex maritime environments - Shuhui Hao; Wei Guan; Xianku Zhang; Zhewen Cui; Sheng Qu (Ocean Engineering, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Genome-wide interactions with cadmium exposure in dysglycemia: populational effects and molecular insights - Qi Jiang; Bin Li; Yunfei Ma; Wanying Shi; Liang Ding; Naifan Hu; Yunhao Zhao; Yingli Qu; Zheng Li; Peijie Sun; Yifu Lu; Donghui Zhang; et al. (Journal of Hazardous Materials, 2026)

Chronic Arsenic Exposure Induced Reproductive Toxicity by Promoting Ferroptosis and the Protective Effects of Xylo-Oligosaccharides - Xin Jiang; Yuanbin Wang; Jianyu Qu; Ying Ma; Xin Sheng; Jine Yi; Ji Wang; Lixin Wen; Rongfang Li; Shuiping Liu (Biological Trace Element Research, 2026)

Iron and zinc isotopic insights into the formation of Archean continental crust - Jianfeng Ma; Hamed Gamaleldien; Robert H. Smithies; Tim Johnson; Yuan-Ru Qu; Sheng-Ao Liu; Christopher L. Kirkland (Earth and Planetary Science Letters, 2026)

Ammonium may emerge as the primary driver of future aerosol acidity, replacing the historical role of sulfate over the coastal area of North China: Insights from a megacity (Qingdao) - Wenshuai Li; Yaoyu Song; Tianshu Chen; Yuxuan Qi; Guanru Wu; Xinshuo Wang; Wenwen Xie; Lifang Sheng; Wencai Wang; Wenjun Qu; Yang Zhou (Atmospheric Environment, 2026)

A framework to detect tillage practices from space: A demonstration in the US Midwest - Xiaocui Wu; Qu Zhou; Kaiyu Guan; Sheng Wang; James Hipple; Bin Peng; Zhangliang Chen; Rongzhu Qin (Remote Sensing of Environment, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

The contributions of two fertilization events to the fertilization recovery efficiency in Arabidopsis - Yuan Wang; Yaxiao Liu; Wenhao Li; Han Lu; Li-Jia Qu; Sheng Zhong (Science China Life Sciences, 2026)

Association Between Exposure to Multiple Metal Elements and Cognitive Function in Older Adults: The Mediating Role of Branched-Chain Amino Acids - Weixuan Yang; Qianru Xie; Miaomiao Wei; Yadi Yang; Mingzhi Liu; Wenjing Cao; Sufang Wang; Qu-nan Wang; Fangbiao Tao; Jie Sheng (Biological Trace Element Research, 2026)

Heterogeneous agent proximal policy optimization for UAVs-USV formation navigation with multi-modal perception - Zhewen Cui; Wei Guan; Shuhui Hao; Tongbo Hu; Sheng Qu; Xianku Zhang (Ocean Engineering, 2026)

An integrated strategy for the efficient extraction and stabilization of phycocyanin from Limnospira platensis - Yuan-Yuan Li; Zhen-Wei Shi; Sheng-nan Yin; Hai-Bin Ren; Zi-Han Qu; Di-Feng Ren (Journal of Applied Phycology, 2026)

The Application of Iron(III)-Tetraamidomacrocyclic Ligand/Peroxide System for Rapid In-situ Degradation of Groundwater Bisphenols - Chao Wang; Kun Liu; Zemin Zhang; Li Nie; Feng Sheng; Fengxiao Zhu; Xiru Chen; Changsheng Qu (Bulletin of Environmental Contamination and Toxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unveiling the gut-brain axis: How chronic exposure to arsenic-induced microglial pyroptosis drives Alzheimer's disease-like pathology - Jianyu Qu; Xin Jiang; Ying Ma; Xin Sheng; Changyi Pi; Yuanbin Wang; Qiurong Xu; Rican Li; Peiran Wang; Dongping Qian; Ji Wang; Zili Yi; et al. (Journal of Hazardous Materials, 2026)

Monascus fermentation enhances the lipid-lowering properties of ginseng in vivo and component assay - Qingsong Qu; Qing Zhou; Xinhui Peng; Zhixun Li; Mingyue Jia; Yingying Zhang; Cuiting Yang; Xingxing Dai; Mengke Sheng; Jichuan Kang; Xinyuan Shi (Food Research International, 2026)

Identification of stomatal opening positive regulators in augustinegrass - Dong-Li Hao; Jia Qu; Jun-Qin Zong; Zhi-Yong Wang; Jiang-Shan Hao; Hai-Long Lu; Ying Zhao; Dao-Jin Sun; Sheng-Nan Yang; Jian-Xiu Liu; Li Liao; Ling Li (Horticulture, Environment, and Biotechnology, 2026)

The enrichment and metabolic adaptation of autotrophic denitrifiers in pyrite-induced biofilms enhances TN removal and reduces carbon demand in A2/O systems - Huize Guan; Caiyan Qu; Jingyu Liu; Sheng Hu; Xi Tang; Di Wu; Chong-Jian Tang (Chemical Engineering Journal, 2026)

Synthesis and leaching evaluation of entropy-stabilized zirconolite Ca(Zr,Hf,Sn)xTi3-xO7 (x = 0.8–2.2) - Qu Ai; Shi-Kuan Sun; Yu Tian; Wei-Dong Xiao; Yi Zhao; Sheng-Heng Tan; Wei-Ming Guo; Hua-Tay Lin (Chemical Engineering Journal, 2026)

The collaborative navigation decision-making method of USV by UAV based on improved PPO algorithm - Sheng Qu; Wei Guan; Tongbo Hu; Zhewen Cui (Ocean Engineering, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Origami-inspired deployable spatial structures with terrain adaptability - Yichen Wang; Xiaolei Wang; Haibo Qu; Buqin Hu; Chin-Hsing Kuo; Sheng Guo (Engineering Structures, 2025)

Link between Double-Diffusive Staircases and Water Masses in the Arctic Ocean - Xue-Long Song; Sheng-Qi Zhou; Ling Qu; Yuan-Zheng Lu; Lu-Dan Pan (Thalassas: An International Journal of Marine Sciences, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

A novel strain-based deformation monitoring method for subsea free-spanning pipelines - Tao Jiang; Zi-min Xie; Jia-jian Wang; Dong-sheng Li; Chun-xu Qu (Engineering Structures, 2025)

Research on Collision Avoidance Method of USV Based on UAV Visual Assistance - Tongbo Hu; Wei Guan; Chunqi Luo; Sheng Qu; Zhewen Cui; Shuhui Hao (Journal of Marine Science and Engineering, 2025)
Collision avoidance technology serves as a critical enabler for autonomous navigation of unmanned surface vehicles (USVs). To address the limitations of incomplete environmental perception and inefficient decision-making for collision avoidance in USVs, this paper proposes an autonomous collision avoidance method based on deep reinforcement learning. To overcome the restricted field of view of USV perception systems, visual assistance from an unmanned aerial vehicle (UAV) is introduced. Perception data acquired by the UAV are utilized to construct a high-dimensional state space that characterizes the distribution and motion trends of obstacles, while a low-dimensional state space is established using the USV’s own state information, together forming a hierarchical state space structure. Furthermore, to enhance navigation efficiency and mitigate the sparse-reward problem, this paper draws on the trajectory evaluation concept of the dynamic window approach (DWA) to design a set of process rewards. These are integrated with COLREGs-compliant rewards, collision penalties, and arrival rewards to construct a multi-dimensional reward function system. To validate the superiority of the proposed method, collision avoidance experiments are conducted across various scenarios. The results demonstrate that the proposed method enables USVs to achieve more efficient autonomous collision avoidance, indicating strong potential for engineering applications.

Detecting the onset of rice field inundation in the Lower Mississippi River Basin via Harmonized Landsat Sentinel-2 (HLS) satellite time series - Yawen Deng; Bin Peng; Kaiyu Guan; Benjamin R.K. Runkle; Beatriz Moreno-García; Xiaocui Wu; Sheng Wang; Qu Zhou; Michele L. Reba (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Iron and zinc isotopes constrain the continental crust formation - Jianfeng Ma; Hamed Gamaleldien; Sheng-Ao Liu; Yuan-Ru Qu (Geochimica et Cosmochimica Acta, 2025)

Application of dielectric discharge barrier plasma: A technique for reducing microorganisms, improving antioxidant capacity, and inhibiting softening of winter jujube - Jing Qian; Shuang Deng; Wenfeng Qu; Xiaowei Sheng; Wenjing Yan; Jianhao Zhang; Jin Wang (Food Research International, 2025)

Vibration isolation method based on local resonance mechanism for near-field piling in rail transport - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Soil Dynamics and Earthquake Engineering, 2025)

TSC2/mTORC1 integrates deoxynivalenol signals recognized by membrane receptors IR and EGFR to restrict intestinal stem cell function - Cai-xia Dou; Hao-zhan Qu; Ying-chao Qin; Xiao-fan Wang; Hui-chao Yan; Run-sheng Li; Yu-guang Zhao; Jia-yi Zhou; Xiu-qi Wang (Journal of Hazardous Materials, 2025)

Pivotal roles of intracellular Cl− in COVID-19: pathogenesis and therapeutic targets - Su Qu; Lei Chen; Jie Sheng; Xiao-Chun Hou; Wen-Liang Zhou; Nan-Shan Zhong; Yi-Lin Zhang (Science Bulletin, 2025)

Genomic and antifungal analysis of Bacillus velezensis CX-H3: a promising biocontrol agent for maize Fusarium root rot - Wenxia Dong; Yiping Shi; Xinyi Li; Siyu Qu; Feng Wang; Chengze Sheng; Yuqi Ren; Longbin Zhou; Weimin Hu (Physiological and Molecular Plant Pathology, 2025)

Temperature and Precipitation Change over South China in CMIP5 and CMIP6 Models: Historical Simulation and Future Projection - Dongdong Peng; Tianjun Zhou; Sheng Hu; Lixia Zhang; Jiayu Zheng; Jingxuan Qu (Advances in Atmospheric Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Calibration method for radiation signal of LiDAR mapping in 3D ocean space - Qiusheng Fang; Jundong Zhang; Xiaolei Wang; Zhenchao Qu; Jun Sheng (Marine Geophysical Research, 2025)

Synergistically networked 1D/2D/3D phase change composites with Ultra-Fast contactless thermal energy conversion and enhanced electromagnetic interference shielding performance - Xinpeng Hu; Bin Ai; Bingqing Quan; Zhanjin Shi; Zhigang Liu; Mengjie Sheng; Yang Ding; Han Yan; Yang Xiao; Gangchen Lu; Shuang Liu; Hao Wu; et al. (Chemical Engineering Journal, 2025)

Nitrogen uptake by Scenedesmus quadricauda and its responses over environmental factors - Pengbo Zhao; Xiaofei Lou; Yafei Cui; Chang Wu; Chenyu Song; Jingyuan Cui; Sheng Zhang; Yao Qu; Tao Peng; Ruihong Chen; Haiping Zhang (Marine Pollution Bulletin, 2024)

Co-toxicity and co-contamination remediation of polycyclic aromatic hydrocarbons and heavy metals: Research progress and future perspectives - Xiyao Qu; Qiuya Niu; Cheng Sheng; Mengmeng Xia; Chengxu Zhang; Xiaolin Qu; Chunping Yang (Environmental Research, 2024)

An efficient flavonoid glycosyltransferase NjUGT73B1 from Nardostachys jatamansi of alpine Himalayas discovered by structure-based protein clustering - Mingkang Feng; Yuan Liu; Bin He; Hairong Zhong; Axiang Qu-Bie; Min Li; Mengting Luo; Xiaoming Bao; Ying Li; Xinjia Yan; Huachun Sheng; Zhifeng Zhang; et al. (Phytochemistry, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

Durable flame retardant and UV-resistant coating for Poly (ethylene terephthalate) fabric with recyclability and reusability - Yulong Qu; Feng Chen; Xiaowei Su; Jian Liu; Xiaoyu Gu; Hongfei Li; Jun Sun; Peng Qi; Sheng Zhang (Chemical Engineering Journal, 2024)

From satellite-based phenological metrics to crop planting dates: Deriving field-level planting dates for corn and soybean in the U.S. Midwest - Qu Zhou; Kaiyu Guan; Sheng Wang; James Hipple; Zhangliang Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Manipulating Förster interactions between the π-D and π-A Exciplex-Forming hosts and dopants by substituent steric optimization for highly efficient Orange-Red OLEDs - Zi-Qi Feng; Sheng-Yi Yang; Min Song; Zhi-Hao Qu; Zi-Yu Song; Zuo-Quan Jiang; Dong-Ying Zhou; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Ba2+ doping into Ni/Al2O3 nanofibers promotes CO2 methanation via alkaline modulation - Mengyuan Zhang; Xiaoyan Lu; Ying Qu; Chuandong He; Jiali Dong; Kongliang Luo; Jian Ye; Nana Lu; Qiang Niu; Pengfei Zhang; Sheng Dai (Chemical Engineering Journal, 2024)

SLCOBNet: Shrimp larvae counting network with overlapping splitting and Bayesian-DM-count loss - Yang Qu; Sheng Jiang; Daoliang Li; Ping Zhong; Zhencai Shen (Biosystems Engineering, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

New geographical records and molecular investigation of the ciliate Spirostomum - Sheng-Bo Zhou; Zhi-Yu Zhao; Ping Guan; Bo Qu (Protist, 2024)

Complete genome sequence of Kushneria phosphatilytica YCWA18T reveals the P-solubilizing activity of the genus Kushneria - Guang-xun Du; Wen-sheng Yu; Ji-kun Su; Guo-chong Liu; Ping Gao; Xu-guang Hong; Ling-yun Qu (Marine Genomics, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Effects of internal waves on bottom thermal structures and turbulent mixing in the Xisha Islands - Ming-Quan Zhu; Xian-Rong Cen; Sheng-Qi Zhou; Yuan-Zheng Lu; Shuang-Xi Guo; Peng-Qi Huang; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Investigation of a haze-to-dust and dust swing process at a coastal city in northern China part II: A study on the solubility of iron and manganese across aerosol sources and secondary processes - Mingge Sun; Yuxuan Qi; Wenshuai Li; Wenqing Zhu; Yiyan Yang; Guanru Wu; Yanjing Zhang; Yunhui Zhao; Jinhui Shi; Lifang Sheng; Wencai Wang; Yingchen Liu; et al. (Atmospheric Environment, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Zinc isotope evidence for enhanced organic carbon burial driving transient oxygenation of the Mesoproterozoic ocean - Kexin Song; Dandan Li; Yi-Wen Lv; Chengshuai Yuan; Yuan-Ru Qu; Sheng-Ao Liu (Precambrian Research, 2024)

Scalable fabrication of multifunctional polylactic acid fibrous membranes with enhanced superhydrophobicity and radiative cooling performance - Xiaolong Li; Yu Du; Mengjie Sheng; Heng Xie; Ting Wu; Jinping Qu (Journal of Cleaner Production, 2024)

Dextral shear initiation of the Kangguer Shear Zone in the East Tianshan: Constraints from a “porphyroclast” system - Bo Liu; Zhengle Chen; Mengmeng Qu; Feng Yuan; Awei Mabi; Mingqiang Sheng; Jing Liu; Fengbin Han; Wengao Zhang; Hailong Huo (Journal of Asian Earth Sciences, 2024)

Exploring near-bottom turbulent mixing across the Challenger Deep based on temperature spectral analysis - Yuan-Zheng Lu; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Jian Lin; Xian-Rong Cen; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Do degraded grasslands provide a better habitat for plateau pika? —Testing the nutritional hypothesis - Zaiwei Wang; Jiawen Yan; Matthew Pawley; Dianne H.Brunton; Jiapeng Qu; Cyril C. Grueter; Jin-Sheng He; Weihong Ji; Zhibiao Nan (Agriculture, Ecosystems & Environment, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Microbial mechanisms in nitrogen fertilization: Modulating the re-mobilization of clay mineral-bound cadmium in agricultural soils - Jun-Feng Wang; Can Liu; Zhi-Min Xu; Fo-Peng Wang; Yun-Yun Sun; Jia-Wei Huang; Qu-Sheng Li (Science of The Total Environment, 2024)

Increased risk of heavy metal accumulation in mangrove seedlings in coastal wetland environments due to microplastic inflow - Jia-Wei Huang; Yun-Yun Sun; Qu-Sheng Li; Huan-Zhan Zhou; Yi-Hao Li; Xiang-Xiang Fan; Jun-Feng Wang (Environmental Pollution, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Experimental investigation and numerical analysis on the confined deflagration behavior of methane-air mixtures within the suppression of typical haloalkanes - Tao Wang; Yuhuai Sheng; Yingying Yu; Fangming Cheng; Xuhan Ding; Jiao Qu; Jun Deng; Fan Nan; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Urea reduces the sustainability of soil Cd immobilization by upregulating the expression of AmSTOP1 and AmMATE genes in edible amaranth roots - Fo-Peng Wang; Jun-Feng Wang; Tao He; Ping Tian; Xiao-Qian Song; Qu-Sheng Li (Environmental Pollution, 2024)

Correlation of Gut Microbiota with Children Obesity and Weight Loss - Li-Jun Peng; Yan-Ping Chen; Fang Qu; Yan Zhong; Zhi-Sheng Jiang (Indian Journal of Microbiology, 2024)

A Highly Efficient and Energy Saving Electrochromic Platform for Adaptive Visible and Near-Infrared Light Modulation - Dajiang Tang; Junxin Wang; Xiaoyu Huang; Dashui Zhang; Sheng Cao; Linfei Yin; Zhangfa Tong; Hongbing Ji; Rachel C. Evans; Hui-Ying Qu (Chemical Engineering Journal, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Accurate genomic selection using low-density SNP panels preselected by maximum likelihood estimation - Shiyu Qu; Sheng Lu; Yang Liu; Ming Li; Songlin Chen (Aquaculture, 2024)

Carveol alleviates osteoarthritis progression by acting on synovial macrophage polarization transformation: An in vitro and in vivo study - Sheng Chen; Hanqing Xu; Yi He; Chen Meng; Yunhui Fan; Yunkun Qu; Yingguang Wang; Wei Zhou; Xiaojian Huang; Hongbo You (Chemico-Biological Interactions, 2024)

Uptake, translocation, accumulation, and metabolism of fluroxypyr-meptyl and oxidative stress induction in rice seedling - Zhao Jie Chen; Hao Wen Wang; Si Ying Li; Yong Heng Zhang; Ya Nan Qu; Zhi Hai He; Xue Sheng Li; Xiao Liang Liu (Environmental Science and Pollution Research, 2023)

Improved eutrophication model with flow velocity-influence function and application for algal bloom control in a reservoir in East China - Jingyuan Cui; Hanling Xu; Yafei Cui; Chenyu Song; Yao Qu; Sheng Zhang; Haiping Zhang (Journal of Environmental Management, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Dual reinforced composite membranes from in-situ ionic crosslinked quaternized chitosan filled quaternized polyvinylidene fluoride nanofiber for alkaline direct methanol fuel cell - Ying Ou; Ting Qu; Fan Cheng; Haiyang Yang; Fuqiang Hu; Jie Wang; Hai Liu; Guoliang Liu; Sheng Wen; Chunli Gong (Carbohydrate Polymers, 2023)

Fluviispira vulneris sp. nov., isolated from human wound secretions - Peijuan Tang; Na Peng; Pengwen Ouyang; Sheng Long; Zhenhua Wei; Xingchun Chen; Pinghua Qu; Liangyi Xie (Antonie van Leeuwenhoek, 2023)
Human infections by environmental bacteria is becoming an increasing problem and has become a matter of great concern due to the adverse effects worldwide. In this study, we reported a new environmental pathogen. Isolate GX5518 T was a novel Gram-negative, aerobic, non-motile, pleomorphic and red-pigmented bacterium, was isolated from human wound secretions (GuangXi, People’s Republic of China). Growth occurred at pH 6.0–8.0 (optimum, pH 7.0) and 10–37 °C (optimum, 28–32 °C) with 0–1.5% (w/v) NaCl in R2A agar. Comparative analysis of the 16S rRNA gene sequences revealed that isolate GX5518 T was closely related to Fluviispira sanaruensis JCM 31447 T (99.73%) and Fluviispira multicolorata 33A1-SZDP T (98.49%). However, the estimated ANI values of the isolate GX5518 T compared to the F. sanaruensis JCM 31447 T and F. multicolorata 33A1-SZDP T were 88.67% and 77.35%, respectively. The estimated dDDH, ANI and AAI values between isolate GX5518 T and its closely related strains were below the threshold values generally considered for recognizing a new species. The genome size was 3.6 Mbp and the DNA G + C content was 33.1%. The predominant fatty acids (> 5%) in GX5518 T cells were iso-C 15:0 , C 16:0 , C 17:0 , C 17:1 ω 8 c and C 16:1 ω 7 c /C 16:1 ω 6 c . The major menaquinone was MK-8 (86.9%). The polar lipids were phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and three unknown lipids (L1-3). The chemical composition was different from that of the F. sanaruensis JCM 31447 T . Comparative genomics analysis between isolate GX5518 T and its related strains revealed that there were a number of genes involved in resistance to antibiotics and toxic compounds in isolate GX5518 T , which were responsible for the copper homeostasis, cobalt-zinc-cadmium resistance, resistance to fluoroquinolones, and zinc resistance. Based on the phenotypic, chemotaxonomic, and genomic analyses, isolate GX5518 T (= CGMCC 1.18685 T = KCTC 82149 T ) represents a novel species of the genus Fluviispira , for which the name Fluviispira vulneris sp. nov. is proposed.

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Camel skin-fat structure inspired MXene@PVA/PCC aerogel composite for efficient medium and low temperature infrared stealth - Qinghong Ji; Xinxin Sheng; Xiaolong Li; Shuang Liu; Qiufei Chen; Pengzong Guo; Yabi Yang; Youyou Huang; Guoliang Zhang; Xiang Lu; Jinping Qu (Chemical Engineering Journal, 2023)

Arsenic pollution, geochemical fractions, and leaching characteristics in soil samples from four contaminated sites in the Beijiang River Basin, South China - Yu-Zhong Liu; Jun-Feng Wang; Han-Yun Fan; Tao He; Dao-Yuan Wang; Huan-Zhan Zhou; Qu-Sheng Li (Environmental Science and Pollution Research, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Tree-inspired and scalable high thermal conductivity ethylene–vinyl acetate copolymer/expanded graphite/paraffin wax phase change composites for efficient thermal management - Xinpeng Hu; Xianrong Huang; Bingqing Quan; Chuanbiao Zhu; Youqiang Yang; Mengjie Sheng; Chao Ding; Haoye Wen; Xiaolong Li; Jingang Wei; Hao Wu; Xiang Lu; et al. (Chemical Engineering Journal, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

A new strategy to study geochemical characteristics and migration of crude oils in Zhu I Depression, Pearl River Mouth Basin, South China Sea - Xuanbo Gao; Siyuan Di; Xianfeng Tan; Wanfeng Zhang; Jia Wang; Long Luo; Xuejiao Qu; Jianping Liu; Shengyu Li; Nan Jiang; Sheng He; Shukui Zhu (Organic Geochemistry, 2023)

Carbonate-silicate interaction in subducting slabs recorded by Zn isotopes in western Alps metasediments - Yuan-Ru Qu; Sheng-Ao Liu; Vincent Busigny; Ze-Zhou Wang; Fang-Zhen Teng (Earth and Planetary Science Letters, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Genomic prediction of survival against Vibrio harveyi in leopard coral grouper (Plectropomus leopardus) using GBLUP, weighted GBLUP, and BayesCπ - Sheng Lu; Yang Liu; Shiyu Qu; Qian Zhou; Lei Wang; Tianshi Zhang; Wenteng Xu; Mengqian Zhang; Yu Song; Jie Wang; Chunhua Zhu; Songlin Chen (Aquaculture, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Effects of sand sedimentation and wind erosion around sand barrier: Numerical simulation and wind tunnel test studies - Kai Zhang; Hai-long Zhang; Yu-hui Deng; Jian-jun Qu; Zheng-hui Wang; Sheng Li (Journal of Mountain Science, 2023)

A novel covalent polymerized phase change composite with integrated shape memory, self-healing, electromagnetic shielding and multi-drive thermal management functions - Yu Fang; Zhuolin Li; Xiaolong Li; Hao Wu; Mengjie Sheng; Xiang Lu; Jinping Qu (Chemical Engineering Journal, 2023)

PM2.5 source apportionment identified with total and soluble elements in positive matrix factorization - Wenshuai Li; Yuxuan Qi; Wen Qu; Wenjun Qu; Jinhui Shi; Daizhou Zhang; Yingchen Liu; Yanjing Zhang; Weihang Zhang; Danyang Ren; Yuanyuan Ma; Xinfeng Wang; et al. (Science of The Total Environment, 2023)

Airborne hyperspectral imaging of cover crops through radiative transfer process-guided machine learning - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Chongya Jiang; Qu Zhou; Kaiyuan Li; Ziqi Qin; Elizabeth A. Ainsworth; Jingrui He; Jun Wu; Dan Schaefer; Lowell E. Gentry; et al. (Remote Sensing of Environment, 2023)

Cross-scale sensing of field-level crop residue cover: Integrating field photos, airborne hyperspectral imaging, and satellite data - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Qu Zhou; Sibo Wang; Xiaocui Wu; Chongya Jiang; Bin Peng; Weiye Mei; Kaiyuan Li; Ziyi Li; Yi Yang; et al. (Remote Sensing of Environment, 2023)

Towards operational atmospheric correction of airborne hyperspectral imaging spectroscopy: Algorithm evaluation, key parameter analysis, and machine learning emulators - Qu Zhou; Sheng Wang; Nanfeng Liu; Philip A. Townsend; Chongya Jiang; Bin Peng; Wouter Verhoef; Kaiyu Guan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Sulfate and nitrate elevation in reverse-transport dust plumes over coastal areas of China - Wenshuai Li; Yuxuan Qi; Wen Qu; Wenjun Qu; Jinhui Shi; Daizhou Zhang; Yingchen Liu; Feng Wu; Yuanyuan Ma; Yanjing Zhang; Danyang Ren; Xueqing Du; et al. (Atmospheric Environment, 2023)

Recent cover crop adoption is associated with small maize and soybean yield losses in the United States - Jillian M. Deines; Kaiyu Guan; Bruno Lopez; Qu Zhou; Cambria S. White; Sheng Wang; David B. Lobell (Global Change Biology, 2023)
Cover crops are gaining traction in many agricultural regions, partly driven by increased public subsidies and by private markets for ecosystem services. These payments are motivated by environmental benefits, including improved soil health, reduced erosion, and increased soil organic carbon. However, previous work based on experimental plots or crop modeling indicates cover crops may reduce crop yields. It remains unclear, though, how recent cover crop adoption has affected productivity in commercial agricultural systems. Here we perform the first large‐scale, field‐level analysis of observed yield impacts from cover cropping as implemented across the US Corn Belt. We use validated satellite data products at sub‐field scales to analyze maize and soybean yield outcomes for over 90,000 fields in 2019–2020. Because we lack data on cover crop species or timing, we seek to quantify the yield impacts of cover cropping as currently practiced in aggregate. Using causal forests analysis, we estimate an average maize yield loss of 5.5% on fields where cover crops were used for 3 or more years, compared with fields that did not adopt cover cropping. Maize yield losses were larger on fields with better soil ratings, cooler mid‐season temperatures, and lower spring rainfall. For soybeans, average yield losses were 3.5%, with larger impacts on fields with warmer June temperatures, lower spring and late‐season rainfall, and, to a lesser extent, better soils. Estimated impacts are consistent with multiple mechanisms indicated by experimental and simulation‐based studies, including the effects of cover crops on nitrogen dynamics, water consumption, and soil oxygen depletion. Our results suggest a need to improve cover crop management to reduce yield penalties, and a potential need to target subsidies based on likely yield impacts. Ultimately, avoiding substantial yield penalties is important for realizing widespread adoption and associated benefits for water quality, erosion, soil carbon, and greenhouse gas emissions.

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Characterization of Water Transport in Porous Building Materials Based on an Analytical Spontaneous Imbibition Model - Ming-Liang Qu; Sheng-Yue Lu; Qingyang Lin; Sajjad Foroughi; Zi-Tao Yu; Martin J. Blunt (Transport in Porous Media, 2022)

Diffusion-seepage coupling model and its application of oil-bed gas in coal seam with overlapping resources - Yong lu Suo; Hui sheng Qu; Lang Liu; Ying kai Liu (Arabian Journal of Geosciences, 2022)

Galectin-1 Contributes to Vascular Remodeling and Blood Flow Recovery After Cerebral Ischemia in Mice - Yin-hong Cheng; Yi-fan Jiang; Chuan Qin; Ke Shang; Yuan Yuan; Xian-jie Wei; Zhe Xu; Xiang Luo; Wei Wang; Wen-sheng Qu (Translational Stroke Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Aberrant activity within auditory network is associated with psychiatric comorbidities in interictal migraineurs without aura - Heng-Le Wei; Yu-Chen Chen; Yu-Sheng Yu; Xi Guo; Gang-Ping Zhou; Qing-Qing Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2021)

Suppression of multiple reflection–refraction waves in the shallow low-velocity zone via vertical source combination - Suoliang Chang; Zhen Qu; Sheng Zhang; Yanning Fu; Qiang Chen (Acta Geophysica, 2021)

Rubus chingii var. suavissimus alleviates high-fat diet-induced lipid metabolism disorder via modulation of the PPARs/SREBP pathway in Syrian golden hamsters - Man-Jing Jiang; Li Li; Wan-Fang Huang; Jian Su; Yao-Hua Li; Xiao-Sheng Qu; Lan-Lan Fan (Journal of Natural Medicines, 2021)

Nitrogen fertilizer management affects remobilization of the immobilized cadmium in soil and its accumulation in crop tissues - Jun-Feng Wang; Wan-Li Li; Qu-Sheng Li; Li-Li Wang; Tao He; Fo-Peng Wang; Zhi-Min Xu (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Advances in physiological functions and mechanisms of (−)-epicatechin - Zhihao Qu; Ailing Liu; Penghui Li; Changwei Liu; Wenjun Xiao; Jianan Huang; Zhonghua Liu; Sheng Zhang (Critical Reviews in Food Science and Nutrition, 2021)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Impaired functional connectivity of limbic system in migraine without aura - Heng-Le Wei; Jinan Chen; Yu-Chen Chen; Yu-Sheng Yu; Gang-Ping Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2020)

l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Yi-Fan Wang; Jun-Feng Wang; Zhi-Min Xu; Shao-Hua She; Jun-Qing Yang; Qu-Sheng Li (Plant and Soil, 2020)

Phosphate-solubilizing bacteria will not significantly remobilize soil cadmium remediated by weathered coal - Qiong Gao; Qu-Sheng Li; Bao-Yan He; Jun-Qing Yang; Li-Li Wang; Jun-Feng Wang; Jian-Jun Jiang; Dong-Sheng Wang; Yi-Fan Wang (Environmental Science and Pollution Research, 2019)

Cysteine-rich peptides: signals for pollen tube guidance, species isolation and beyond - Sheng Zhong; Li-Jia Qu (Science China Life Sciences, 2019)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Using stable isotopes (δD, δ18O, δ34S and 87Sr/86Sr) to identify sources of water in abandoned mines in the Fengfeng coal mining district, northern China - Shen Qu; Guangcai Wang; Zheming Shi; Qingyu Xu; Yuying Guo; Luan Ma; Yizhi Sheng (Hydrogeology Journal, 2018)

Optimization of a Coupling Process for Insulin Degludec According to a Quality by Design (QbD) Paradigm - Lei Nie; Mingming Hu; Xu Yan; Tingting Guo; Haibin Wang; Sheng Zhang; Haibin Qu (AAPS PharmSciTech, 2018)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Mantle source of the 2.44–2.50-Ga mantle plume-related magmatism in the Fennoscandian Shield: evidence from Os, Nd, and Sr isotope compositions of the Monchepluton and Kemi intrusions - Sheng-Hong Yang; Eero Hanski; Chao Li; Wolfgang D. Maier; Hannu Huhma; Artem V. Mokrushin; Rais Latypov; Yann Lahaye; Hugh O’Brien; Wen-Jun Qu (Mineralium Deposita, 2016)

Causes and controlling pattern of sand hazards at the Danghe Reservoir of Dunhuang in Northwest China - Sheng-bo Xie; Jian-jun Qu; Ying-jun Pang (Journal of Mountain Science, 2016)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Characterizing the compositional variation of dissolved organic matter over hydrophobicity and polarity using fluorescence spectra combined with principal component analysis and two-dimensional correlation technique - Ben-Sheng Su; Zhen Qu; Xiao-Song He; Ying-Hao Song; Li-Min Jia (Environmental Science and Pollution Research, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Association between SMN2 methylation and disease severity in Chinese children with spinal muscular atrophy - Yan-yan Cao; Yu-jin Qu; Sheng-xi He; Yan Li; Jin-li Bai; Yu-wei Jin; Hong Wang; Fang Song (Journal of Zhejiang University-SCIENCE B, 2016)

Effects of freeze-thaw cycles on soil mechanical and physical properties in the Qinghai-Tibet Plateau - Sheng-bo Xie; Qu Jian-jun; Lai Yuan-ming; Zhou Zhi-wei; Xu Xiang-tian (Journal of Mountain Science, 2015)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

HBx and HBs regulate RhoC expression by upregulating transcription factor Ets-1 - Dongdong Qin; Kai Li; Jialin Qu; Sen Wang; Chengcheng Zou; Yanrui Sheng; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Hepatitis B virus regulation of Raf1 promoter activity through activation of transcription factor AP-2α - Jialin Qu; Jianbo Li; Ke Chen; Dongdong Qin; Kai Li; Yanrui Sheng; Chengcheng Zou; Sen Wang; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

The association of polymorphisms on TGFBR1 and colorectal cancer risk: a meta-analysis - Xueli Zhang; Liang Wu; Youhua Sheng; Wenhua Zhou; Zhongming Huang; Jun Qu; Ganglong Gao; Duan Cai; Ming Zhang (Molecular Biology Reports, 2012)

MiR-34a inhibits lymphatic metastasis potential of mouse hepatoma cells - Yanjie Guo; Sheng Li; Jianhua Qu; Shujing Wang; Yibing Dang; Jianhui Fan; Shengjin Yu; Jianing Zhang (Molecular and Cellular Biochemistry, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

L-FABP T94A decreased fatty acid uptake and altered hepatic triglyceride and cholesterol accumulation in Chang liver cells stably transfected with L-FABP - Na Gao; Xia Qu; Jin Yan; Qi Huang; Hao-Yong Yuan; Dong-Sheng Ouyang (Molecular and Cellular Biochemistry, 2010)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Seasonal variation, source, and regional representativeness of the background aerosol from two remote sites in western China - Wenjun Qu; Dan Wang; Yaqiang Wang; Lifang Sheng; Gang Fu (Environmental Monitoring and Assessment, 2010)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

High throughput culture and gametogenesis induction of Laminaria japonica gametophyte clones - Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Shi Ju Luo; Xue Xi Tang (Journal of Applied Phycology, 2008)

Breeding of an elite Laminaria variety 90-1 through inter-specific gametophyte crossing - Quan-Sheng Zhang; Xue-Xi Tang; Yi-Zhou Cong; Shan-Cun Qu; Shi-Ju Luo; Guan-Pin Yang (Journal of Applied Phycology, 2007)

Improvement of sandy soil with water-conserving membrane and its effect on crop growth - Xiu-jun Li; Xiang-hao Cui; Qu-sheng Li (Chinese Geographical Science, 2005)

Sustainable agriculture development in saline-alkali soil area of Songnen Plain, Northeast China - Zhi-chun Wang; Qu-sheng Li; Xiu-jun Li; Chang-chun Song; Guang-xin Zhang (Chinese Geographical Science, 2003)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)